Ethics of Global Health Photography: A Focus on Being More Human - Aubrey P. Graham; James V. Lavery; Robert Cook-Deegan (Harvard FXB Center for Health and Human Rights, 2019)
This article explores the relationship between ethics and the production of global health photographic images. Through the text, we emphasize the need for greater awareness of potential ethical pitfalls, not just in relationship to the finished product of the image but also throughout the full photographic process. In order to do so, we present and explore three vignettes detailing our personal global health photographic experiences. Using these examples of the process of photographic production, we argue that the ethical emphasis needs to fall as much on the way of making and circulating the images as on the resulting images and their content. In showing that ethics starts long before the decision to publish a photograph, we engage global health photography as a relationship built of unequal power dynamics, where agency is held (albeit lopsidedly) by all of those around the camera-the subject, the photographer, and the bystanders or actors who exist beyond the photograph's composition. By following the concept of "encouraging people to do what is best given certain circumstances and constraints," we as photographers and global health workers advocate for a more fully human interaction through conscious, careful global health visual policy and humane photographic deliberation.